Prevalence of insulin resistance in Chinese solar greenhouse and field workers: evidence from a solar greenhouse and field workers study - Yan, Tenglong; Wang, Minghui; Yang, Siwen; Wang, Yuqian; Zhou, Xingfan; Zhu, Xiaojun; Ma, Wenjun; Tang, Shichuan; Li, Jue (Frontiers in Public Health, 2023)
Evidence suggests that agricultural workers are at higher risk of insulin resistance (IR), but few studies have investigated IR in solar greenhouse workers, who are exposed to higher concentrations of agricultural risk factors than traditional agricultural workers. A prevalence study was conducted in a greenhouse vegetable farm in China. In total, 948 participants were enrolled in this study. Among them, 721 participants were allocated to the greenhouse worker group (G group), and 227 participants were assigned to the field worker group (F group). The TyG index, which is an indicator to evaluate prediabetes (IR), was calculated by the formula: TyG index = ln [fasting triglycerides (mg/dL) × fasting plasma glucose (mg/dL)/2]. To evaluate the associations of TyG index alternation with solar greenhouse and field work, multiple linear regression (MLR) and logistic regression models were performed. The TyG index in the G group (8.53 ± 0.56) was higher than that in the F group (8.44 ± 0.59) (p < 0.05). Solar greenhouse work was positively associated with an increased TyG index in both the multiple linear regression model [β = 0.207, (0.006, 0.408)] and the logistic regression model [OR = 1.469, (1.070, 2.016)]. IR was associated with the solar greenhouse work. However, the determination of agricultural hazard factors needs to be further strengthened to improve exposure assessment. Graphical Abstract